Modifiable Risk Factors in Uncontrolled High Blood Pressure Patients of Banjul, Gambia - Jorge Vega Abascal; Yodalis GarcÃ©s Hernandez; Luis Enrique Almaguer Mederos; Yulennis Vega Caballero (Correo Científico Médico)
Introduction: high blood pressure is a risk factor that could lead to cardiovascular disease and stroke.